Edirne Çevresi Halk Ezgilerinin Makam, Ritm Ve Tip İncelemesi - Kumru, Hakan (Sosyal Bilimler Enstitüsü, 2012)
Osmanlı İmparatorluğu'nun 92 yıl boyunca başkenti olan Edirne; bir kültür-sanat ve ilim şehri olarak en görkemli zamanlarını bu dönemde yaşamıştır. Çevre bölgelerden gelen göçlerle beraber, çeşitli kültür alışverişleri olmuş ve bugünkü geleneksel yapıların sağlam temelleri o dönemde atılmıştır. Müzikal yapısı ile de bir kültürlerarası kaynaşma görüntüsü sergileyen Edirne'de, Klasik Türk Müziği ve Mehter Müziği kendini her zaman ve her dönemde hissettirmiştir. Bunun yanı sıra Balkan Müziğiyle de etkileşim halinde olmuştur. ?Edirne Çevresi Halk Ezgilerinin Makam, Ritm ve Tip İncelemesi? başlıklı bu tezde; bölgedeki renkli ve kaynaşmış müzikal yapıların ortaya çıkarılması hedeflenmiş; makam/dizi, ritm ve tip(biçim) yapıları üzerine analitik bir çalışma yapılarak bölge müzik karakteri incelenmeye çalışılmıştır.

As a culture, art and science city, Edirne, wich was the capital of Ottoman Empire for 92 years, lived its most magnificent times in this period. With the migration coming from the surrounding regions, there had been various cultural relations and strong bases of today?s traditional stuctures were laid at that period. In Edirne, that showed an intercultural agitational image with its musical structure, classical Turkish Music and Mihter Music [Ottoman Historical Music] made itself felt everytime and every period. Besides, it had been in affection with the Balkan Music. In this thesis with the title `?The Investigation of Modal, Rhythm and Type of Folk Tunes Around Edirne?? bringing the regional colourful and agitated musical structures to the light is aimed; regional musical character has been tried to be investigated by doing an analitical study on modal, rhythm and type structures.
The Investigation Of Modal, Rhythm And Type Of Folk Tunes Around Edirne
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2012
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Social Sciences, 2012
Keywords: Halk Bilimi (Folklor); Müzik; Edirne; Ezgi; Halk müziği; Makamlar; Müzik; Müzik eserleri; Müzik kültürü; Ritm; Tipoloji; Folklore; Music; Edirne; Intonation; Folk music; Modes; Music; Music works; Music culture; Rhythm; Typology